Association between urinary symptoms and severity of urinary incontinence in Brazilian women - Alves, Ana Letícia; Frota, Isabella Parente Ribeiro; da Costa, Ana Virginia Marques; Nascimento, Simony Lira; Figueiredo, Vilena Barros de (Fisioterapia & Saúde Funcional, 2025)
Introduction: Urinary Incontinence (UI) is an involuntary loss of urine, being a global health problem. Investigate the association between urinary symptoms and severity is essential for the treatment. Objective: To evaluate associations between urinary symptoms and the severity of urinary incontinence in Brazilian women. Methods: Observational and cross-sectional study, based on the observation of medical records in a retrospective manner. A sample composed of women assisted by the Outpatient Pelvic Physiotherapy Service of the Maternity School Assis Chateaubriand. Data were analyzed and analyzed by Jamovi 1.2.25 software and with an alpha of significance less than 0.05. Descriptive analysis was performed for continuous variables, frequencies, and percentages for categorical variables. Mann-Whitney or Kruskal-Wallis test for continuous variables and Fisher's exact test for categorical variables. Results: A total of 400 women with a mean age of 55 years (±12.2) participated in the study, with Mixed Urinary Incontinence (MUI) being the most prevalent diagnosis (44.5%). There was a significant difference for the association of the presence of urinary symptoms in the severity of urinary incontinence, and positive between the measures of severity comparisons. Conclusion: It is concluded that there is an association between urinary symptoms and the severity of UI in women.